2017
DOI: 10.1098/rspb.2017.0357
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and body size shift in Mediterranean bivalve assemblages: unexpected role of biological invasions

Abstract: Body size is a synthetic functional trait determining many key ecosystem properties. Reduction in average body size has been suggested as one of the universal responses to global warming in aquatic ecosystems. Climate change, however, coincides with human-enhanced dispersal of alien species and can facilitate their establishment. We address effects of species introductions on the size structure of recipient communities using data on Red Sea bivalves entering the Mediterranean Sea through the Suez Canal. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…Such intervals of higher nutrient availability would allow the development of larger body size [52] -a scenario which is in sharp contrast to the prediction of temperature-induced reduction in body size for the same time interval. On a similar line, Nawrot et al [53] demonstrated a size increase in the Mediterranean mollusc due to warming induced invasion. The effect of global warming indirectly led to an increase in the large bivalve species in the Mediterranean Sea by facilitating the entry and subsequent spread of tropical aliens.…”
Section: Absence Of Size Reduction During Events Of Climatic Warmingmentioning
confidence: 77%
“…Such intervals of higher nutrient availability would allow the development of larger body size [52] -a scenario which is in sharp contrast to the prediction of temperature-induced reduction in body size for the same time interval. On a similar line, Nawrot et al [53] demonstrated a size increase in the Mediterranean mollusc due to warming induced invasion. The effect of global warming indirectly led to an increase in the large bivalve species in the Mediterranean Sea by facilitating the entry and subsequent spread of tropical aliens.…”
Section: Absence Of Size Reduction During Events Of Climatic Warmingmentioning
confidence: 77%
“…, Nawrot et al. ). Interpreted in combination with the results from a recent study on coral‐coral spatial competition, where the best models also do not predict spatial competition outcomes well even though they do so significantly better than random (Precoda et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, North American Pacific coast bivalves with larger body sizes appear more likely to become established outside their initial ranges since the Pleistocene (Roy et al 2001, 2002). In recent, human-mediated introductions into the Mediterranean Sea, successful invaders from the Red Sea were larger than native taxa (Nawrot et al 2017). Because we know body size to be phylogenetically conserved in bivalves (Saulsbury et al 2019), these patterns suggest colonizers may be more closely related to one another than expected from random.…”
Section: Discussionmentioning
confidence: 99%